The efficacy of bleb needling revision with 5-fluorouracil in encapsulated bleb after unsuccessful trabeculectomy - Okka, Mehmet; Mirza, Enver; Oltulu, Refik; Belviranlı, Selman; Gündüz, Mehmet Kemal (The European Research Journal, 2019)
Objectives: To investigate the efficacy of the bleb needling revision (BNR) procedure with the adjunctive use of 5-Fluorouracil (5-FU) in encapsulated bleb after unsuccessful trabeculectomy.Methods: We reviewed 16 eyes of 15 subjects who underwent BNR procedure due to encapsulated bleb after unsuccessful trabeculectomy. Demographic data, type of glaucoma, intraocular pressure (IOP) values of pre-BNR, IOP values of post-BNR at first day, first week and first month, follow up time and complications were recorded from patients’ files, retrospectively. Results: The mean follow up time was 53.1 ± 26.4 weeks. The average time between previous unsuccessful trabeculectomy and BNR was 11.12 ± 8.79 weeks. The mean IOP of pre-BNR was 26.0 ± 4.4 mmHg and significantly decreased to 12.4 ± 5.0 mmHg post-BNR at the first day (p < 0.001). The mean IOP values of post-BNR at the first week was 13.3 ± 4.9 mmHg and at the first month was 14.8 ± 4.8 mmHg. According to the mean IOP of pre-BNR, the mean IOP values of post-BNR at the first week and at the first month were significantly lower (p < 0.001 and p < 0.001, respectively). Seven (44%) eyes were achieved success and eight (50%) eyes were achieved qualified success. One (6%) eye was classified as the failure. Conclusion: The bleb needling revision procedure with the adjunctive use of 5-FU in encapsulated bleb after unsuccessful trabeculectomy is a simple, useful and repeatable method to restore the dysfunctional bleb.